2014
DOI: 10.1186/s12920-014-0064-y
|View full text |Cite|
|
Sign up to set email alerts
|

FLAGS, frequently mutated genes in public exomes

Abstract: BackgroundDramatic improvements in DNA-sequencing technologies and computational analyses have led to wide use of whole exome sequencing (WES) to identify the genetic basis of Mendelian disorders. More than 180 novel rare-disease-causing genes with Mendelian inheritance patterns have been discovered through sequencing the exomes of just a few unrelated individuals or family members. As rare/novel genetic variants continue to be uncovered, there is a major challenge in distinguishing true pathogenic variants fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 63 publications
(86 reference statements)
1
106
0
1
Order By: Relevance
“…Of genes previously not implicated in neurodevelopmental disorders we find that DNMs in the gene HECW2, identified in one of our trios, has also been identified in patients in five previous studies, while no DNMs have been found in controls. Among the previously reported variants in HECW2 all had a CADD score >15 (range [15][16][17][18][19][20][21][22][23][24][25][26][27]. To more formally evaluate the finding of DNMs in HECW2 in our trios and previous studies, we used the statistical framework developed by Samocha et al 14 Using the 5338 trio families collated above together with our 39 trios yields an expected number of DNMs (non-synonymous and stopgains) in HECW2 of 0.7, while we observed a total of six nonsynonymous mutations ( p-value = 6.11×10 e-5 ).…”
Section: Trio Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Of genes previously not implicated in neurodevelopmental disorders we find that DNMs in the gene HECW2, identified in one of our trios, has also been identified in patients in five previous studies, while no DNMs have been found in controls. Among the previously reported variants in HECW2 all had a CADD score >15 (range [15][16][17][18][19][20][21][22][23][24][25][26][27]. To more formally evaluate the finding of DNMs in HECW2 in our trios and previous studies, we used the statistical framework developed by Samocha et al 14 Using the 5338 trio families collated above together with our 39 trios yields an expected number of DNMs (non-synonymous and stopgains) in HECW2 of 0.7, while we observed a total of six nonsynonymous mutations ( p-value = 6.11×10 e-5 ).…”
Section: Trio Sequencingmentioning
confidence: 99%
“…It has previously been shown that disease-causing variants in the OMIM database are enriched for CADD scores higher than 20. 26 To investigate the magnitude of the impact of the DNMs, the CADD scores of the DNMs were compared with the CADD scores of 1000 randomly chosen SNVs. The analysis was performed by randomly picking the same fraction of synonymous, non-synonymous and stopgain SNVs from the ExAC database as the set of mutations identified in this study.…”
Section: Trio Sequencingmentioning
confidence: 99%
“…The performance of our model was also assessed by scoring the probability of being dominant for well-known false-positives for rare conditions in genome-wide screens, 25 such as genes encoding mucins, taste and olfactory receptors, etc. Out of 436 genes from this set, only 4 had LDA scores higher than J max (Table S6, Figure 2F).…”
mentioning
confidence: 99%
“…And it has been indicated that driver genes are related to not only mutation frequency, but also mutation context or gene length [25] and variants tend to arise more frequently in long genes [26]. For example, TTN, the longest gene in human genome, accumulates many variants just due to its length [24,26]. TTN may be selected in many computational methods; however, it usually serves as passenger gene [27].…”
Section: Introductionmentioning
confidence: 99%